The hidden cost of venture capital - Emilie Aguirre (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
Founders, employees, consumers, and even funders increasingly expect businesses to pursue social goals alongside financial performance. Yet even the most committed firms have found it difficult to maintain social performance over time. Scholars in economics, management, and law have put forth several explanations for this "mission drift," including inappropriate governance, poor management, lack of genuine commitment, and threat of takeovers. Puzzlingly, research to date primarily focuses on later-stage firms, even though the events and decisions that take place in a firm's early stages can critically impact retention of its social performance. Drawing from over five years of qualitative field research at six firms, this Article argues that a company's early-stage financing can have lasting consequences for social performance. I find that the structure of VC - the most prestigious and coveted form of startup funding - shifts organizational focus toward prioritizing rapid growth and exit, implicitly crowding out firm social performance. I find this dynamic occurs even when VCs package themselves as "impact investors" committed to preserving social performance. This study underscores the need to reorient impact VC models and startup corporate governance to avoid losing sight of social aspirations. It also has implications for corporate law and finance more broadly, challenging whether the current legal system operates optimally to achieve efficiency, promote innovation, and serve societal goals.
Keywords: 330